Molecular MLVA Typing of Typical and Genetically Altered Natural Strains of Vibrio cholerae El Tor Biovar - T. A. Kul’Shan’; Ya. M. Krasnov; Yu. V. Lozovsky; N. I. Smirnova (Проблемы особо опасных инфекций, 2012)
Displayed is the possibility of differentiation between typical and genetically altered strains of Vibrio cholerae biovar El Tor, which vary in their virulence and epidemic potential, by means of MLVA. Determined is a significant genetic diversity of the gene-variants, probably, due to their polyclonal origin and continuous alterations within genome under the influence of varying environmental factors.